Impact of soil conservation adoption on intrahousehold allocations in Zambia - Conor Carney; Monica Harber Carney (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
In this paper, we examine the impact of soil conservation adoption on gender-specific resource allocations within households in Zambia. The extension of funding of conservation farming (CF) training sessions in 2007 in specific districts in Zambia provides variation in CF takeup. We use this variation to implement a difference-in-differences strategy on a number of datasets. We show that expansion of funding for CF training sessions increased take-up of CF, increased female labour hours, and shifted household expenditures towards goods associated more strongly with female preferences than male preferences. These results stress the importance of understanding the impact of development programmes, specifically promotion of agricultural technologies, on household gender dynamics.
Keywords: J2; J43; N57; Q16; 330; agricultural technology adoption; gender roles; Zambia